2D CFD-PBM simulation of hydrodynamic and particle growth in an industrial gas phase fluidized bed polymerization reactor - Akbari, V.; Borhani, T.N.G.; Shamiri, A.; Aramesh, R.; Hussain, Mohd Azlan; Abd Hamid, M.K. (Elsevier, 2015)
In an industrial fluidized bed polymerization reactor, particle size distribution (PSD) plays a significant role in the reactor efficiency evaluation. The computational fluid dynamic (CFD) models coupled with population balance model (CFD-PBM) have been extensively employed to highlight its potential to analyze the industrial-scale gas phase polymerization reactor (FBRs) utilizing ANSYS Fluent software. The predicted results reveal an acceptable agreement with the observed industrial data in terms of pressure drop and bed height. Courant number independent study has been carried out to record the mesh and time step independent results for large scale FBRs. Furthermore, the minimum fluidization velocity (U-mf) and size-dependent particle growth rate have been assessed to emphasize the impact of PSD along the reactor. The results show transient regime in the case of minimum fluidization velocity. The simulation results signify that in order to improve the polymerization yield, the amount of gas velocity can be increased without change in the fluidization regime, i.e. segregation. Hence, the 2D CFD-PBWDQMOM coupled model can be used as a reliable tool for analyzing and improving the design and operation of the gas phase polymerization FBRs. (C) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.